2014
DOI: 10.1111/evo.12494
|View full text |Cite
|
Sign up to set email alerts
|

THE EVOLUTION OF ENVIRONMENTAL TOLERANCE AND RANGE SIZE: A COMPARISON OF GEOGRAPHICALLY RESTRICTED AND WIDESPREADMIMULUS

Abstract: The geographic ranges of closely related species can vary dramatically, yet we do not fully grasp the mechanisms underlying such variation. The niche breadth hypothesis posits that species that have evolved broad environmental tolerances can achieve larger geographic ranges than species with narrow environmental tolerances. In turn, plasticity and genetic variation in ecologically important traits and adaptation to environmentally variable areas can facilitate the evolution of broad environmental tolerance.We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
155
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(162 citation statements)
references
References 55 publications
2
155
0
1
Order By: Relevance
“…Besides living in areas where greater climate change is expected, Primates in the Amazon are climatic and geographically restricted and thereby expected to be more sensitive to climate change [7,17,49]. In addition, these species will probably be unable to keep pace with climate change even at relatively low magnitude of climate change due to high velocity of climate change expected in the tropics and poor dispersal abilities [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Besides living in areas where greater climate change is expected, Primates in the Amazon are climatic and geographically restricted and thereby expected to be more sensitive to climate change [7,17,49]. In addition, these species will probably be unable to keep pace with climate change even at relatively low magnitude of climate change due to high velocity of climate change expected in the tropics and poor dispersal abilities [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…2013) and should therefore display elevated phenotypic variation and plasticity (Sheth and Angert 2014) relative to rare species. The increased phenotypic variation found in widespread species was due to both strong spatial structure (>3× increase in among‐population variance relative to rare species) and increased phenotypic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…A high degree of plasticity will expand the amount of suitable habitat (Baker and Stebbins 1965; Pohlman et al. 2005; Sheth and Angert 2014), and studies have shown that increased plasticity can be beneficial when invading new sites (Loomis and Fishman 2009), surviving stress (Heschel et al. 2004), or persisting through changing environmental conditions (Chevin and Lande 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ability to adapt when the environment changes, is the result of their genetic diversity, condition that needs to be studied. Insufficient diversity would lead species to restrict their geographic distribution and be more vulnerable to extinction under novel selection pressure (Sheth and Angert, 2014). Small populations with low diversity might also experience higher levels of inbreeding (Oleas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%